Favorable response to trastuzumab plus irinotecan combination therapy in two patients with HER2-positive relapsed small-cell lung cancer. Issue 3 (March 2015) - Kinehara, Yuhei; Minami, Toshiyuki; Kijima, Takashi; Hoshino, Shigenori; Morimura, Osamu; Otsuka, Tomoyuki; Hayama, Yoshitomo; Fukushima, Kiyoharu; Takeuchi, Yoshiko; Higashiguchi, Masayoshi; Miyake, Kotaro; Hirata, Haruhiko; et al.
Highlights Standard therapeutic strategies for relapsed-SCLC remain unestablished. HER2 is reported to be a negative prognostic factor of extensive disease-SCLC. This case report first shows the potential of trastuzumab-based therapy in SCLC. Antitumor effects of trastuzumab are presumed to be caused mainly by ADCC.